Pelatihan Geotagging dan Layout Peta untuk Organisasi Perangkat Daerah Kabupaten Ogan Ilir: Geotagging and Map Layout Training for Regional Apparatus Organizations in Ogan Ilir Regency - Natul, Al Shida; Sastra, Ahmad Ridho; Aryantoni, Johan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Geospatial data and technology are critical in a country's sustainable development process. Regional Apparatus Organizations (OPD) are essential in implementing regional government, which requires knowledge and understanding of geospatial data and technology to support better decision-making in a region. One way is through Geotagging training for ODP to increase knowledge, utilization, and competency in human resources in the geospatial field. The target of this training is the Ogan Ilir Regency OPD in South Sumatra Province. Training is held face-to-face using lecture and practice methods. Participants are given modules and receive direct guidance during the training process. The output of this training shows a significant increase in participants' understanding of geospatial data and the use of geotagging both theoretically and practically, which can be assessed from the presentation of the results of the tasks they have completed. This activity is a provision for ODP Kab. Ogan Ilir to be able to manage geospatial data and information.